Associations Between Dental Occlusion and Nutritional Status in Community-Dwelling Older Adults (P01-017-19). (13th June 2019) - Zelig, Rena; Sackey, Joachim; Parikh, Nevil; Hoskin, Eileen; Singer, Steven; Touger-Decker, Riva
Abstract: Objectives: This study explored associations between dental occlusion and nutritional status in community dwelling older adults. Methods: This cross-sectional study utilized data from electronic health records (EHR) of new patients (>65 years), who presented for care at the Rutgers School of Dental Medicine between June 1, 2015 and June 30, 2018. The self-administered Mini Nutritional Assessment (Self-MNA) score (as a measure of nutritional status), clinical and demographic information were obtained from the EHR. Tooth number and location were recorded based on odontogram and digital radiographs. Spearman's rho, Kruskal-Wallis, and Chi Square tests were used to explore relationships between variables. Results: Of the 238 records reviewed, complete data (MNA score, tooth number and location) were available for 140 (58.8%). The mean age of participants was 72.78 years (SD = 5.58); 55% were female. The mean MNA score was 12.15 (SD = 2.14); 24.3% were at risk for malnutrition, and 5% were malnourished. The mean number of teeth (excluding 3 rd molars) was 17.01 (SD = 8.72); 21.4% had 0–9 teeth, 30% had 10–19 teeth, and 48.6% had 20–28 teeth. Thirty-five % had no posterior occlusion (POP); 27.1% had no anterior occlusion (AOP). MNA score was weakly but significantly correlated with number of POP ( r  = 0.21, P  = 0.02). Those with 10–19 teeth had significantly lower MNA scores then those with 20 or more teeth ( P  = 0.003). Being at risk of malnutrition or malnourished was associated with having 10–19 teeth, while normal nutritional status was associated with having 20 or more teeth ( P  = 0.02). Conclusions: In this sample of older adults, those with 10–19 teeth were more likely to be at risk of malnutrition or malnourished. Similarly, as number of POP decreased, MNA score decreased. Research utilizing a larger sample to further explore the relationships between tooth loss and nutritional status is warranted. Funding Sources: Sackler Institute for Nutritional Sciences, New York Academy of Science.